LEVERAGE, ROA DAN KEPEMILIKAN INSTITUSIONAL PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Nurcahyati, Sinta Dea; Mohklas, Mohklas (STIE PENA, 2022)
This study aims to analyze the effect of leverage, Return On Assets (ROA), and institutional ownership on firm value. The data analysis method uses panel data regression. The population in this study are companies whose shares remain incorporated in the LQ-45 index and must always be actively traded every day during the 2017-2020 period. The sample in this study used purporsive sampling method, in order to obtain a sample of 112 data. The conclusion in this study is that leverage has no significant effect on firm value, Return On Assets (ROA) has a significant effect on firm value, institutional ownership has no significant effect on firm value and leverage, Return On Assets (ROA) and institutional ownership simultaneously affect the value of the firm. company.Keywords : Leverage, Return On Asset (ROA), Institutional Ownership, Value Company